2008
DOI: 10.1111/j.1369-1600.2007.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

PRECLINICAL STUDY: Age‐dependent differences in sensitivity and sensitization to cannabinoids and ‘club drugs’ in male adolescent and adult rats

Abstract: Lifelong substance abuse is often initiated during adolescence; yet, most pre-clinical research in this area has been conducted in adult animals. Substantial evidence exists that the brain development that continues throughout adolescence may result in pharmacological responses that differ in a crucial manner from those of adults. The goal of this study was to evaluate age differences in motor activity following acute and repeated administration of drugs that are commonly abused by adolescents, including cocai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 40 publications
(42 reference statements)
6
23
0
Order By: Relevance
“…These findings are in line with data showing an age-dependent susceptibility, with a higher sensitivity of 5-HT neurons to MDMA-induced toxicity and an increased lethality in adult rats compared to adolescent rats [Broening et al, 1994;Wiley et al, 2008]. Altogether, there seems to be a biphasic vulnerability to MDMA-induced apoptotic cell death in the developing rat brain.…”
Section: Discussionsupporting
confidence: 80%
“…These findings are in line with data showing an age-dependent susceptibility, with a higher sensitivity of 5-HT neurons to MDMA-induced toxicity and an increased lethality in adult rats compared to adolescent rats [Broening et al, 1994;Wiley et al, 2008]. Altogether, there seems to be a biphasic vulnerability to MDMA-induced apoptotic cell death in the developing rat brain.…”
Section: Discussionsupporting
confidence: 80%
“…Some studies have reported that exposure to these compounds fails to enhance their behavioral effects (Arnold et al, 1998;Varvel et al, 2007;Wiley et al, 2008), although others have demonstrated sensitization (Cadoni et al, 2001(Cadoni et al, , 2008Rubino et al, 2001). Differences in the doses and compounds administered during exposure may account for some of the different findings reported.…”
Section: Introductionmentioning
confidence: 46%
“…Since previous work demonstrated reduced locomotor stimulation in adolescents to psychostimulants such as cocaine (Laviola et al, 1995; Izenwasser and French, 2002; Wiley et al, 2008; Zombeck et al, 2009) and methamphetamine (Zombeck et al, 2009), it was hypothesized that periadolescent animals would exhibit reduced stimulant effects to PCP or ketamine when compared to adults. Surprisingly, young periadolescent animals (PND 30) exhibited a greater stimulant response to an acute administration of either PCP or ketamine when compared to older adolescents (PND 38) or adults (PND 60).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, adolescents show reduced locomotor stimulation and less sensitization than adults to psychostimulants such as cocaine (Laviola et al, 1995; Izenwasser and French, 2002; Wiley et al, 2008; Zombeck et al, 2009) and methamphetamine (Zombeck et al, 2009). Age differences in the development of sensitization to dissociatives have not been well studied and are therefore less understood.…”
Section: Introductionmentioning
confidence: 99%